Guaraná - Paullinia cupana (H.B.K): Study on the status of oxidation of powder and smoked sticks - Gomes da Silva, Wilson; Rovellini, Pierangela; Fusari, Paola; Venturini, Stefania (Revista de Ciências Agroveterinárias, 2015)
The guaraná, Paullinia cupana, HBK – is the fruit of the guarana plant, and is native to the Amazon region. It grown in particular in the communities of Maués. Currently production is spread throughout the states of Bahia, Pará, and Mato Grosso. The ripe fruits are collected and placed in containers where water is added to facilitate the separation of the pulp that covers the seeds. After this treatment they are placed in the sun for drying. Then after they are transferred into a frying pan of metal or brick kilns heated with firewood to complete the hassle/roasting. Guaraná is marketed in the form of seeds, powder and smoked sticks. In folk medicine it is used in powder for the following properties: a dietary food, stimulating organic, for the presence of caffeine, analgesic, antipyretic, anti-fermentation, diuretic, antioxidant, and vascular tonic and considered the elixir of life. In the food industry, it is used in the preparation of extracts, syrups, and soft drinks. Lately the consumption of guaraná has had a significant increase in both Brazil and abroad. The evaluation of the oxidation of foods that contain oils and fats is a parameter needed in quality and stability evaluation in order to ensure food safety. The chemical structure of guaraná is mostly unsaturated therefore susceptible to oxidation. Considering the lack of data in the literature refering to secondary oxidation of foodstuffs, the objective of this work was to evaluate the total content of fatty acids oxidized in the form of guaraná powder and stick. The determination was performed by HPLC-UV. The results of the analysis of oxidation of the powder samples and sticks are different depending on the time of collection, preparation mode and preservation system. We propose new research with ripe fruits selected and processed in place to make it possible to decrease the oxidative status.